Thermal behavior and decay performance of wood modified with poly(ethyl cyanoacrylate). Issue 6 (2nd November 2022) - Can, Ahmet; Sivrikaya, Hüseyin; Hazer, Baki
ABSTRACT: Ethyl cyanoacrylate polymerizes at room temperature, and is often used as an adhesive in many areas for a wide variety of applications. In this study, the possibility of using poly(ethyl cyanoacrylate) in the field of wood modification was investigated. For this purpose, Scots pine ( Pinus sylvestris L.) and Oriental beech ( Fagus orientalis ) samples were impregnated with poly(ethyl cyanoacrylate) that was synthesized using acetone. Modified samples were characterized by Thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and Scanning Electron Microscopy (ESEM). Decay performance was done with white rot fungus ( Trametes versicolor (L: Fr.) Pilat. (FFPRI 1030)) for beech wood and brown rot fungus Coniophera puteana for pine wood; the European standard EN113 FTIR analysis indicated that PECA could appreciably alter the chemical structure in modified wood. Thermal changes in modified wood were be minor compared to those of untreated wood. Samples treated with PECA had significantly lower mass losses than untreated samples as a result of fungal exposure to Coniophora puteana and T. versicolor .